2019
DOI: 10.1128/jvi.00322-19
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus V Protein Degrades Mitochondrial Antiviral Signaling Protein To Inhibit Host Type I Interferon Production via E3 Ubiquitin Ligase RNF5

Abstract: Paramyxovirus establishes an intimate and complex interaction with the host cell to counteract the antiviral responses elicited by the cell. Of the various pattern recognition receptors in the host, the cytosolic RNA helicases interact with viral RNA to activate the mitochondrial antiviral signaling protein (MAVS) and subsequent cellular interferon (IFN) response. On the other hand, viruses explore multiple strategies to resist host immunity. In this study, we found that Newcastle disease virus (NDV) infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 58 publications
2
63
0
Order By: Relevance
“…Regardless of how the interaction is induced, once the complex is complete, innate immune antiviral responses can ensue via activation of IRF-3 and NF-κB signaling [157,158]. MAVS can be sent off for proteasomal mediated degradation by several E3 ubiquitin ligases including the E3 ligases Ring Finger Protein 5 (RNF5) and membrane-associated ring finger (C3HC4) 5 (MARCH5) [159,160]. In the absence of iRhom2, murine innate immunity to Vesicular Stomatitis Virus (VSV) infection was considerably impaired leading to neurological symptoms in all iRhom2 deficient mice compared to 60% of wild-type mice.…”
Section: Mavs and Stingmentioning
confidence: 99%
“…Regardless of how the interaction is induced, once the complex is complete, innate immune antiviral responses can ensue via activation of IRF-3 and NF-κB signaling [157,158]. MAVS can be sent off for proteasomal mediated degradation by several E3 ubiquitin ligases including the E3 ligases Ring Finger Protein 5 (RNF5) and membrane-associated ring finger (C3HC4) 5 (MARCH5) [159,160]. In the absence of iRhom2, murine innate immunity to Vesicular Stomatitis Virus (VSV) infection was considerably impaired leading to neurological symptoms in all iRhom2 deficient mice compared to 60% of wild-type mice.…”
Section: Mavs and Stingmentioning
confidence: 99%
“…NDV strains are classified as velogenic, mesogenic, or lentogenic strains. It has been reported that NDV suppresses the innate immune response through V protein-mediated MDA5, phospho-STAT1 and MAVS degradation ( 1 , 2 ). NDV is reported to have distinct influences on dendritic cells (DCs) during the early stage of NDV infection, including activation of the DCs and cross-priming of naïve T cells into tumor-specific T cells ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is implicated in ERAD, cell motility and also negative regulation of autophagy and ER stress (27)(28)(29)(30). Several studies have shown the connection between RNF5 and antiviral response: RNF5 negatively regulates virustriggered signaling by targeting STING and MAVS for ubiquitination and degradation at mitochondria (31,32); Newcastle Disease Virus V Protein degrades MAVS by recruiting RNF5 to polyubiquitinate MAVS (33). So far, we have limited knowledge about whether RNF5 could function as the E3 ligase of viral proteins to regulate viral release.…”
Section: Introductionmentioning
confidence: 99%